Электрический импеданс электроакустического преобразователя - Данилов, В.В.; Иванов, С.В. (Технология и конструирование в электронной аппаратуре, 2000)
Коэффициент передачи пьезопреобразователя можно рассчитать по результатам определения его входного импеданса. In engineering calculation of electrical coupling coefficient of electromechanical systems will form "upper electrode - piezotransducer - coupling layers waveguide" the inaccuracy up to 300% occur because of the used Q-factor measurements and its low values. In the article theoretical basis and experimental check of possibility of basic characteristics definition for such systems by input impedance determination results have been presented.